Fundamentals of engineering economic analysis - White, John A.; Grasman, Kellie S.;Case, Kenneth E.;Needy, Kim LaScola;Pratt, David B. (Hoboken, New Jersey : Wiley, 2014)
"Fundamentals of Engineering Economics, 1st Edition provides streamlined topical coverage with a modern and pedagogically-rich presentation. This text features a tight integration of Excel along with a wealth of real world vignettes to reinforce how students will use economics in their future careers. Fundamentals of Engineering Economics, 1st Edition provides enough content for every instructor to choose his/her favorite topics, but is streamlined enough to feel approachable to students. A pedagogically-rich approach combined with strong digital offerings make the course manageable, leaving students with the Engineering Economics knowledge needed for future careers"
An overview of engineering economic analysis -- Time value of money calculations -- Equivalence, loans, and bonds -- Present worth -- Annual worth and future worth -- Rate of return -- Replacement analysis -- Depreciation -- Income taxes -- Inflation -- Break-even, sensitivity, and risk analysis -- Captial budgeting.
Includes index.
Keywords: ENGINEERING ECONOMY